Development of Penginyongan Culture as Islamic Socio-Educational Capital in Building Harmony of Indigenous Peoples in Banyumas Raya - Roqib, Moh.; Mardliyah, Layla; Muyasaroh, Hanifah; Muna, Moh. Nailul; Sugiarti, Iis (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Tensions and conflicts are recurring challenges in multicultural and multireligious societies, particularly in regions marked by substantial cultural diversity. In this context, local wisdom rooted in indigenous communities functions as a vital form of Islamic socio-educational capital that can foster social harmony. This research is grounded in the assumption that indigenous cultural values, when articulated within an Islamic ethical framework, play a strategic role in shaping peaceful coexistence. The purpose of this study is to analyze the development of Penginyongan culture as a socio-educational strategy for strengthening harmony among indigenous communities in Banyumas Raya from an Islamic perspective. This study employs a qualitative field research Design, with data collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted using an ethnographic approach, supported by symbolic interactionism and the constant comparative method to capture the dynamic meanings embedded in cultural practices. The findings demonstrate that the development of Penginyongan culture operates through three interconnected strategies: survival strategies aimed at preserving cultural identity, structural strategies institutionalized within social and religious structures, and network strategies that reinforce communal solidarity. These strategies foster collective awareness and sustained community participation in spiritual and ritual activities. The study concludes that Penginyongan culture nurtures lived religious expressions that integrate individual piety with social piety, thereby strengthening social harmony. The implications of this research suggest that locally rooted Islamic socio-education can serve as a replicable model for conflict mitigation and harmony-building in other pluralistic societies, proving that harmony is not imported but cultivated.